Whirlwind - Dailey, Janet; Kensington Publishing Corp. (New York, NY, 2020)
"At the Alamo Canyon Ranch, set amid the desert foothills of Southern Arizona, the Champion women carry on the family legacy of breeding bucking bulls for the rodeo. In a world where bloodline is everything, love is the only risk worth taking ... Everyones talking about Whirlwind at this years Professional Bull Riders Competition. But the promising young bull is the last thing on Shane Tullys mind once he lays eyes on the lady responsible for bringing Whirlwind to the arena. Beautiful, smart, and sexy as hell, Lexie Champion has this rodeo man hungry for more than the thrill of his next competition. But the daughter of bull rancher Bert Champion wants nothing to do with a daredevil, despite the powerful attraction between them ... After losing her beloved brother to a bull riding accident, Lexie is no stranger to the dangers of rodeo life. Which is why resisting Shanes rugged allure should have been easy. But nothing is simple about her reaction to the handsome cowboy, from their first kiss, to the terrifying moment Lexie watches Shane go down in the ring. Faced with a devastating decision, will Lexie make the ultimate sacrifice for the sake of love?"--Provided by publisher.
Keywords: Sisters; Fiction; Rodeos; Fiction; Man-woman relationships; Fiction; Fiction; Fiction; Bulls; Fiction; Rodeos; Women ranchers; Family-owned business enterprises; Cowboys; Fiction; Man-woman relationships; Fiction; Ranches; Arizona; Fiction; Fiction; Arizona; Fiction; Romance fiction; Western fiction